Effects of Road Interactions on Mate‐Searching Movements and Mate Location Success in an Imperiled Pit Viper (Crotalus horridus) - Elizabeth J. Noble; Anna F. Tipton; Morgan L. Thompson; John R. Powers; Amber A. Stubbs; William L. Tillett II; Jorge A. Vázquez Diosdado; Dominic L. DeSantis (Ecology and Evolution)
ABSTRACT For many species, male mate‐searching movements are among the primary determinants of mate location success, and males often incur significant risks associated with elevated movement during reproductive seasons. In an increasingly human‐modified world, this often includes more frequent interactions with anthropogenic landscape features, such as roadways. While road mortality represents the most direct and easily measured cost of road interactions, pervasive indirect or sub‐lethal costs could carry significant fitness consequences that are more difficult to quantify. We leveraged radio telemetry and accelerometry monitoring to explore the associations between seasonal movement strategies, mate location success, and road interactions in Timber Rattlesnakes (Crotalus horridus) from the piedmont ecoregion of Georgia, USA, where populations are in decline. Males, but not females, significantly elevated measures of movement and the frequency of road interactions during mating seasons, supporting our predictions. By using accelerometers to evaluate fine‐scale activity responses to roads, we identified a positive association between road interactions and male activity that was conserved across behavioral seasons. Unexpectedly, there were no associations detected between mate location success and road interactions. However, underlying variation in male movement measures revealed differing associations between movement and mate location success within road interaction categories. We discuss the possible roles of chemosensory disruption and road avoidance in this system, while emphasizing the need for further sampling and targeted field experiments to boost observations of road interactions and refine our understanding of these associations. Ultimately, our results are the first to directly quantify the relationship between elevated male movement in mate searching efforts and increased road interactions by longitudinally monitored rattlesnakes, despite this trend being widely recognized through observational studies of road mortality. For C. horridus, specifically, roads are implicated as a leading driver of declines range‐wide, and our results further highlight mating seasons as a window of highest vulnerability.